Indicator Microflora of Ducks and Chickens in Home Farm Conditions - Oleksii Shevchenko; Volodymyr Melnyk; Liliana Davydovska; Artem Ushkalov; Liliіa Vygovska; Valerii Ushkalov (Veterinary Sciences and Practices)
The aim of this study was to determine the risks of the circulation of zoonotic bacteria in poultry in homesteads. We selected for the study litter samples (10 samples each) of Muscovy ducks and chickens (Hisex breed) aged 100-110 days. The samples were examined using certified nutrient media and equipment in accordance with international standards: ISO 6887-1:2017; ISO 21528-1:2017; ISO 11290-1:2017; ISO 10273:2017; ISO 6579-1:2017; ISO/FDIS 7218; and DSTU 8534:2015. Litter samples from clinically healthy ducks and chickens were examined for the detection of potentially pathogenic bacteria of the Enterobacteriaceae family, Listeria spp., Enterococcus spp., Pseudomonas aeruginosa. In the studied biomaterial, representatives of Klebsiella spp., Yersinia spp., Salmonella spp., Pseudomonas aeruginosa, Listeria spp. were not detected. The content of Escherichia coli (5.0x105 CFU/g and 6.7x106 CFU/g) and Enterococcus faecalis (2.4x108 CFU/g and 1.2x108 CFU/g), respectively, in chicken and duck litter samples is considered physiological. Bacteriological examination of the droppings of clinically healthy chickens and Muscovy ducks, raised on a free-range homestead revealed no carriers of pathogenic bacteria, indicating that there are no possible risks of unchecked zoonotic pathogen spread from the consumption of "backyard" poultry products. Escherichia coli and Enterococcus faecalis in litter samples are considered to be physiological.